Preparação e caracterização de filmes de platina metálica preparados utilizando o método dos precursores poliméricos - Freitas Sobrinho, Renato Garcia de (2006)
In this work we present the preparation and characterization of Pt electrodes deposited onto Ti, obtained by the polymeric precursor method. This route is based on the dissolution of hexachloride platinum acid (H2PtCl6.7H2O) and citric acid in ethylene glycol at different molar ratios. In order to measure the effect of the preparation variables on the electrode surface areas a factorial design 23 was used. We observed the formation of a Pt metallic film, which is uncommon using this procedure. The X-ray diffraction analysis showed the presence of Pt pattern peaks. Besides, it was observed the presence of the 420 plane in a higher intensity compared to bulk Pt, this indicate orientation. The voltametric profile of Ti/Pt and Pt bulk was the same. The electrocatalytical behavior for methanol oxidation in Ti/Pt showed an enhancement of the oxidation current density peak, which increased by 165,5% compared to bulk Pt. Otherwise, the current density peak for ethanol oxidation on Ti/Pt is smaller than on Pt. But in this case the reaction starts 0.11 V more negative than the same process on the bulk Pt. In a second stage, Ti/RuO2(x)Pt(1-x) electrodes were prepared to study the electrocatalytical behavior of the system. Electrochemical experiments showed that the catalytic activity of the mixed electrodes with 87.5 mol % of RuO2 toward methanol oxidation is higher than Ti/Pt.